1997
DOI: 10.1007/s11745-997-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Elution factors of synthetic oxotriacylglycerols as an aid in identification of peroxidized natural triacylglycerols by reverse‐phase high‐performance liquid chromatography with electrospray mass spectrometry

Abstract: Selected elution factors were determined for model oxotriacylglycerols as an aid in identification of the peroxidation products of natural triacylglycerols by reverse-phase high-performance liquid chromatography (HPLC) with electrospray mass spectrometry (LC/ES/MS). For this purpose synthetic triacylglycerols of known structure were converted to hydroperoxides, hydroxides, epoxides, and core aldehydes and their dinitrophenylhydrazones by published procedures. The oxotriacylglycerols were resolved by normal-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 26 publications
4
64
0
Order By: Relevance
“…This would indicate that the sn-2 isomer eluted before the sn-1,3 isomers. This is in complete agreement with the discussion by Sjovall et al (20), in which they reported that the 2-isomer eluted ahead of the 1,3-isomers for aldehydes and hydroperoxy species, although the elution factors tabulated and pictured for the 2-isomers (20) were longer than the elution factors for the corresponding 1,3-isomers.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This would indicate that the sn-2 isomer eluted before the sn-1,3 isomers. This is in complete agreement with the discussion by Sjovall et al (20), in which they reported that the 2-isomer eluted ahead of the 1,3-isomers for aldehydes and hydroperoxy species, although the elution factors tabulated and pictured for the 2-isomers (20) were longer than the elution factors for the corresponding 1,3-isomers.…”
Section: Resultssupporting
confidence: 92%
“…These two classes could not be distinguished by mass. One approach to identification of core aldehydes has been demonstrated by Sjovall and co-workers (20,21). It will be possible to perform the separation on the unreacted oxidation products mixture and on the reacted product mixture to identify which peaks disappear from the chromatogram of the unreacted mixture and appear at different retention times in the reacted mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Much of our present understanding of the role of TAGs comes from measurement of either the total quantity of TAG present in cells, or fatty acids that can be released from TAGs after isolation and saponification rather than knowledge of changes in unique TAG molecular species. In recent years there has been renewed interest in the development of mass spectrometric methods using electrospray ionization and atmospheric pressure chemical ionization to analyze TAGs at the molecular species level [16][17][18][19]. We recently reported a strategy using MS 3 to analyze TAGs from a complex mixture as the NH 4 + adduct ions generated by electrospray ionization [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the volatility of some TAGs, especially those containing polyunsaturated fatty acyl groups, require very high temperatures (Ͼ300°C) to elute from a gas chromatograph, which can lead to decomposition in the well known ester pyrolysis reaction. More recently, electrospray ionization and atmospheric pressure ion-ization have been employed to analyze TAGs at the molecular species level using considerably gentler conditions° [12][13][14][15].°Notable°advances°were°made°by°Han and°Gross° [16]°and°Hsu°and°Turk° [17]°using°lithium adducts of TAGs with collisional activation of the [M ϩ Li] ϩ ions to yield diacyl product ions that revealed specific information about acyl groups esterified to individual TAG molecular species. Also, Byrdwell and Neff employed MS 3 to study the composition of synthetic°TAG°species° [18].°Cheng,°Gross,°and°Pittenauer used high-energy collisions of ammonium and sodium adducts of TAGs to elucidate acyl position on the glycerol backbone and double-bond location of unsaturated°acyl°moieties° [19]°of°pure°TAG°molecular°spe-cies.…”
mentioning
confidence: 99%